Implementation of Legal Protection Against Default Cases Regarding Disputes in Debt and Receivable Agreements (Case Study of Collateral Objects in the Governance of Debt Agreements in the Village Scope) - Raden Ajeng Diah Puspa Sari (CV. Rayyan Dwi Bharata, 2023)
The process of accounts payable which is an agreement between one party and another party and the object being agreed is generally money. The position of one party is the party providing the loan (creditor), while the other party is the party receiving the loan (debtor). The essence of the debt agreement is that the creditor lends money to the debtor, and the debtor is obliged to return it within a predetermined time accompanied by interest. Debt repayments are made in monthly installments. If there is an obstacle regarding debt repayment or there is no effort to be able to pay the debt, an element of default occurs. This discussion will also review further the cases that often occur in rural areas regarding borrowing debts in the village environment.